Deformation and Support Analysis of Headrace Tunnels in Three Tectonic Zones of Nepal: An Empirical and Numerical Approach - Shrestha, Ijan; Jha, Balkrishna; Koju, Aashika; Mishra, Aanand Kumar; Kafle, Nirmal (Journal of Nepal Hydrogeological Association, 2025)
Tunneling in the Himalayan region presents significant engineering challenges due to complex geological formations, high seismicity, and variable rock mass conditions. This study focuses on the comparative analysis of headrace tunnels (HRTs) in three distinct geological regions of Nepal: the Siwaliks, the Lesser Himalayas, and the Higher Himalayas. The primary objective of this study is to evaluate stresses due to tunnel excavation, required support systems, and displacement in these distinct geological settings. The methodology used in this study includes empirical, and numerical approaches to assess tunnel performance in the selected regions. Finite Element Analysis (FEA) was performed to assess tunnel stability, in-situ stresses, and effectiveness of support systems. The findings show significant variations in stress generated, displacement, and required support systems across the three geological regions. The comparative analysis indicates that tunnels in weaker rock formations, like those in the Siwaliks, require substantial support systems, whereas tunnels in the Higher Himalayas experience higher in-situ stresses. This study highlights the behavior of rock masses, the consequent stresses and displacements and the required support systems in the three geological settings when constructing tunnels of the same shape and size.